Lower segment large myoma complicating pregnancy: a case report. - Sharma, P; Gurung, G; Amatya, A; Rana, A (Journal of Institute of Medicine Nepal, 2007)
Background: Uterine myoma is becoming a common problem during pregnancy as the age at first pregnancy is seen in the increasing age and low parity. Case report: We have encountered a 33 years old primi gravida whose cervical myoma was detected during pregnancy and was confirmed at the time of emergency caesarean at term. She was found out to have cervical myoma during the operation. The full text of this paper is available at Journal of Institute of Medicine website